2012
DOI: 10.1784/insi.2012.54.5.278
|View full text |Cite
|
Sign up to set email alerts
|

A data-based modelling scheme for estimating residual stress from Barkhausen noise measurements

Abstract: BARKHAUSENBarkhausen noise measurement is an intriguing technique for the non-destructive testing of material properties. It is applicable to ferromagnetic materials and shown to be sensitive to many material properties. Typically, some features are calculated from the Barkhausen noise signal and compared to the material properties. However, the results are mainly qualitative. In this study, quantitative prediction of residual stress based on the Barkhausen noise measurement is studied. The studied material is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The traditional features computed are the RMS value, peak width, and peak position. Peak height is not used here because it is reported to have a great correlation with the RMS value [5] and thus does not provide any additional information for the model. The sweep measurements were taken from five locations on each sample.…”
Section: Measurements and Data Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional features computed are the RMS value, peak width, and peak position. Peak height is not used here because it is reported to have a great correlation with the RMS value [5] and thus does not provide any additional information for the model. The sweep measurements were taken from five locations on each sample.…”
Section: Measurements and Data Pre-processingmentioning
confidence: 99%
“…Some studies were identified in the literature that modelled material properties and BN. In [2] and [5] for example, linear models were identified for mapping the interactions between BN, and residual stress and hardness. Use of nonlinear model structures can also be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional MBN features such as root mean square (RMS) and MBN energy are often used for stress detection [9,10].…”
Section: Comparison With Traditional Mbn Featuresmentioning
confidence: 99%
“…The Barkhausen effect specifically refers to the phenomenon in which the magnetic flux of a magnetized material changes discontinuously due to magnetic domain inversion during magnetization [ 1 ]. As an important nondestructive testing (NDT) method, the magnetic Barkhausen noise (MBN) signal is sensitive to the changes in many material properties and has many applications in the fields of material stress and hardness detection [ 2 , 3 , 4 , 5 ], metal fatigue state analysis [ 6 ], metal microstructure transformation, and grain size measurement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intensity changes in an MBN signal with material state transformation are usually reflected and described by the representative parameters calculated in time-frequency (TF) domain such as the amplitude, energy, root mean square (RMS), waveform full width at half maximum (FWHM), envelope, peak time, threshold, and power spectrum [ 3 , 4 , 5 , 8 , 9 , 10 ]. However, affected by the microscopic magnetic anisotropy of the material itself, measurement performance, and experimental magnetization parameters (such as magnetization intensity and frequency, excitation waveform), the MBN has an obvious stochastic nature and the application of more automatic signals processing procedures used for extraction, selection, and fusion of signal features containing critical and distinctive information about the material properties are urgently required.…”
Section: Introductionmentioning
confidence: 99%